New possibilities in polymer binder jetting additive manufacturing via infiltration and warm isostatic pressing - Park, Seong Jun (2023)
Binder jetting (BJ) leads to low mechanical properties and high porosity because it uses binders to selectively bind powder materials. To overcome the poor characteristics of BJ parts, infiltration is a generally applied post-process; however, it results in a low infiltration volume and large number of residual voids in the uninfiltrated section. This study aims to effectively improve the mechanical properties, microstructure, and density of polymer-based BJ parts by overcoming limitations of infiltration process via warm isostatic pressing (WIP) that applies heat and pressure. The infiltrated specimens with epoxy are vacuum-packed, and the WIP process is performed at a target temperature of 130 °C and pressure of 8 MPa. Consequently, the infiltration volume increases by up to 195.2%, and the number of residual voids in the uninfiltrated section, where the infiltrants do not reach, is significantly reduced. Further, in terms of the mechanical properties, the tensile strength increases by 1215%, compressive strength by 1280%, and flexural strength by 535%. In addition, the results of transmission, scanning electron microscopy, and microcomputer X-ray tomography reveal a clear decrease in the number of voids.